Komposisi Media Pertumbuhan Protokorm Sebelum Perlakuan Kolkisin untuk Meningkatkan Poliploidi pada Phalaenopsis amabilis (L.) Blume - Putri, Astrid Aditya; Sukma, Dewi; Aziz, Sandra Arifin; Syukur, dan Muhamad (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2018)
Polyploidy induction in Phalaenopsis amabilis is one of the methods to increase plant genetic diversity. A highly meristematic condition of protocorm induced by cytokinines may improve the success rate of polyploidy induction. This experiment was aimed to study the effect of Benzylaminopurine (BAP), Thidiazuron (TDZ) and coconut water (CW) in a half concentration of Murashige & Skoog (MS) medium before colchicine treatment on growth, multiplication and the success rate of polyploidy induction on Phalaenopsis amabilis protocorm. The experiment used completely randomized  design with one factor, medium treatment (15% of CW); 0.51 mg L-1 BAP; 0.50 mg L-1 TDZ; 15% CW + 0.51 mg L-1 BAP; 15% CW + 0.50 mg L-1 TDZ). Each treatment consisted of three replications with five culture bottles of protocorm for each replication and ten protocorms per bottle. The protocorms were incubated for eight weeks in the medium before treated with 50 mg L-1 of colchicine for ten days. The results showed that 15% CW, 15% CW + 0.51 mg L-1 BAP or 0.5 mg L-1 TDZ gave the highest percentage (100%) of alive protocorm. The highest percentage of protocorm multiplication were resulted from 15% CW+0.51 mg L-1 BAP (65.3%) and 15% CW + 0.5 mg L-1 TDZ (62.7%). The best treatment to promote formation of leaves and roots from protocorm was 15% CW. The percentage of polyploid plantlets of 3% was found in plantlet from 15% CW + 0.50 mg L-1 TDZ media treatment while from other treatments could not be detected.Keywords: BAP, chromosome, coconut water, plantlet, TDZ